Would a Euro's Depreciation Improve the French Economy? - Riccardo Magnani; Luca Piccoli; Martine Carré; Amedeo Spadaro (Institute of Labor Economics (IZA), 2017)
In this paper, we use a Micro-Macro model to evaluate the effects of a euro's depreciation on the French economy, both at the macro and micro level. Our Micro-Macro model consists of a Microsimulation model that includes an arithmetical model for the French fiscal system and two behavioral models used to simulate the effects on consumption behavior and labor supply, and a multisectoral CGE model which simulates the macroeconomic effects of a reform or a shock. The integration of the two models is made using an iterative (or sequential) approach. We find that a 10% euro's depreciation stimulates the aggregate demand by increasing exports and reducing imports which increases production and reduces the unemployment rate in the economy. At the individual level, we find that the macroeconomic shock reduces poverty and, to a lesser extent, income inequality. In particular, the decrease in the equilibrium wage, determined in the macro model, slightly reduces the available income for people who have already a job, while the reduction in the level of unemployment permits to some individuals to find a job, substantially increasing their income and, in many cases, bringing them out of poverty.
Keywords: F40; C63; C68; 330; exchange rates; microsimulation; CGE models